THEORETICAL AND METHODOLOGICAL BASIS FOR FORMING THE CULTURE OF SELF-DEPENDENT WORK OF THE PERSON IN THE SYSTEM OF CONTINUOUS EDUCATION - Olga Kozyreva (Вестник Северо-Кавказского федерального университета)
The article defines the features ofthe formation ofthe culture of self-dependent work ofthe individual, presents the generalizing constructs of detailing and visualization of the successful selection of models and technologies for the formation of a culture of self-dependent work of the individual, systematically illustrates the theoretical and methodological foundations for the formation of a culture of self-dependent work of the individual in the system of continuous education, describes adaptive-acme-pedagogical, labor, system-synergetic, personiied approaches, guaranteeing success and the formation of a culture of self-dependent work of the individual in the system of continuous education. The quality of the formation of a culture of self-dependent work of the individual in the system of continuous education is a function and model of optimization of the task of development and self-realization of the individual in the structure of activity and communication, self-afirmation and cooperation, socialization and mutual assistance.